Stable isotope composition of middle Miocene carbonates of the Frontal Cordillera and Sierras Pampeanas: Did the Paranaense seaway flood western and central Argentina? - Ruskin, Brian G. (2011)
The geographic extent, interconnectedness and chronology of the Miocene "Paranaense" epeiric seaway have been the subject of considerable debate. Understanding the timing and location of this marine incursion is significant for documenting sea level changes, paleoclimatic changes, and surface uplift or subsidence. Stable isotope analyses of carbonate strata in the flat-slab segment of the Sierras Pampeanas and high Andean Cordillera, previously purported to be of marine origin, provide evidence that the Paraná seaway did not inundate this portion of west and central Argentina. No unambiguously marine facies or isotopic signatures were recognized for five representative stratigraphic units: the Saguión Formation ESE of Salinas Grande in Córdoba Province; Anta Formation in the Quebrada de la Yesera and Lerma Valley of Salta Province; Del Buey and Del Abra Formations within the Famatina Ranges, La Rioja Province; and Chinches Formation in the Manantiales foreland basin in the Frontal Cordillera, San Juan Province. Paleontologic and lithologic features in support of a marine origin are reconsidered herein. Instead, a lacustrine origin is inferred for these formations, their contemporaneity perhaps related to concurrent global climate conditions and broad tectonic setting. Until more substantive evidence of marine deposition is found, we reject correlation of these units with the Paraná seaway, preserved in the Chaco-Pampean Plain subsurface, and discourage mapping of the seaway as extending into the central Sierras Pampeanas or Andean foreland. Our findings suggest the Miocene Andean foreland was elevated above sea level although it remained as a largely flat-lying area west of the Pampas and Chaco plains, which were inundated by the Paraná seaway.